Nanocomposites Based on Polyethylene and Nanosilver Particles Produced by Metallocenic "In Situ" Polymerization: Synthesis, Characterization, and Antimicrobial Behavior - Rabagliati-Canessa, F; Paez-Collio, M; Paez-Collio, M; Cerda-Villablanca, E; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L; Zapata-Ramirez, P (2011)
Polyethylene nanocomposites containing silver nanoparticles with antimicrobial properties were produced via in situ polymerization. The silver nanoparticles were added together with the catalytic system (metallocene catalyst and methylaluminoxane, MAO, as cocatalyst) directly to the reactor. The polymerization activity did not present significant changes with the incorporation of the silver nanoparticles in comparison to the homopolymerization without filler. The effect of various silver nanoparticle contents on silver ion release and antimicrobial efficacy against Escherichia Coli were studied. Nanocomposites containing higher nanosilver concentrations (5 wt.%) showed the highest silver ion release, and after 24 h reached 99.99% of efficacy against the bacteria compared with the neat PE. Transmission electron microscopy (TEM) images showed that the nanospheres were well dispersed throughout the polyethylene matrix. © 2011 Elsevier Ltd. All rights reserved.